Numerical and Experimental Investigation of Nano zinc Oxide’s Effect on the Mechanical Properties of Chloroprene and Natural Rubber (CR/NR) Composites - Njim, Emad Kadum; Hadi, Fadhel Abbas; Hamzah, Mohsin Noori; Alhilo, Naeem Abdulmohsin; Al-Maamori, Mohammed Hamza (Physics and Chemistry of Solid State, 2024)
Nanocomposites, especially natural rubber (NR), have been extensively studied for their unique features and superior performance in tire applications. The present research investigated the impact of zinc oxide nanoparticles (ZnO) on the performance of typical rotary machine seals made of chloroprene rubber / natural rubber (CR/NR) composites. An ordinary standard rubber two-roll mill and hydraulic press were used to prepare high-temperature vulcanized CR/NR samples filled with ZnO nanoparticles. Tensile strength, tear resistance, abrasion resistance, resilience, and hardness were measured to determine the effects of nanoparticles on these physical and mechanical properties. Based on the various hyperelastic modeling schemes, enhancement in multiple characteristics of the control sample, such as overhaul properties, was observed. Furthermore, results show that increasing nanoparticle content in the vulcanisates increased the physicomechanical characteristics, such as hardness, resilience, tensile strength, and elastic Modulus at 200% strain. Moreover, hyperelastic analytical modeling shows that the differences with experimental results are less than 5%.